Effect of heat treatment on bacteriostatic activity and protein profile of bovine whey proteins. (January 2020) - Xiong, Ling; Li, Chengkang; Boeren, Sjef; Vervoort, Jacques; Hettinga, Kasper
Graphical abstract: Highlights: The bacteriostatic activity of milk serum negatively correlated with intensity of heat treatment. More intense heat treatment was related to decreased retention of native antibacterial proteins. Heating for 30 min above or below 75 °C differently affects both bacteriostatic capacity and native antibacterial proteins. Growth rates of multiple bacteria were negatively correlated with retention of lactoferrin and lactoperoxidase. Abstract: Bovine milk shows bacteriostatic activity mainly due to the presence of antibacterial proteins, like lactoferrin, lactoperoxidase and immunoglobulins. Heat treatment is applied to kill bacteria and thereby extend shelf life of dairy products. Such heat treatment may, however, impair the activity of native antibacterial proteins in milk. The aim of this study was to investigate bacteriostatic capacity and retention of antibacterial proteins in unheated and heated bovine milk. Skim milk samples were heated at 65 °C, 70 °C, 75 °C, 80 °C and 85 °C, for 30 min. Whey was isolated from the heat-treated skim milk and the bacteriostatic capacity of this whey was tested against Streptococcus thermophilus, Escherichia coli, Lactococcus lactis and Pseudomonas fluorescens . The proteomic profile of native whey was determined using LC-MS/MS-based proteomics. Results showed that the bacteriostatic activity of whey negatively correlated with intensity of heat treatment, which was also reflected in the reduced level of native antibacterial proteins. There is a significant difference between milk samples treated for 30 min at <75 °C and milk samples treated at ≥75 °C in both bacteriostatic capacity and native antibacterial proteins. Growth rates of Streptococcus thermophilus, Lactococcus lactis and Pseudomonas fluorescens were negatively correlated with retention of lactoferrin and lactoperoxidase. In conclusion, our study shows that the bacteriostatic capacity of whey decreases with increasing heating intensity, which is strongly correlated with the denaturation of antibacterial proteins. Bacteriostatic activity can be a biomarker for loss of function of antibacterial proteins, and can thereby be used as an indicator for the extent of heat processing of dairy products including antibacterial proteins in a mild heat treatment.